Final results of the EORTC 18871/DKG 80-1 randomised phase III trial: rIFN-α2b versus rIFN-γ versus ISCADOR M® versus observation after surgery in melanoma patients with either high-risk primary (thickness >3 mm) or regional lymph node metastasis - Kleeberg, Ulrich R.; Schadendorf, Dirk (European journal of cancer, 2004)
Between 1988 and 1996, the European Organisation for Research and Treatment of Cancer Melanoma Group (EORTC-MG) performed a prospective, randomised phase III adjuvant trial to evaluate the efficacy and toxicity of low dose recombinant interferon-alpha 2 b (rIFN-α2b) (1 MU) or recombinant interferon gamma (rIFN-γ), (0.2 mg) both given subcutaneously (s.c.), every other day (qod), for 12 months in comparison with an untreated control group. The German Cancer Society (DKG) added a fourth arm with Iscador M®, a popular mistletoe extract. High-risk stage II patients (thickness >3 mm) and stage III patients (positive lymph nodes) without distant metastasis were randomised and followed until their first progression or death. An intention-to-treat analysis was performed. From 1988 to 1996, a total of 830 patients were randomised: 423 in the three-arm EORTC 18871 trial and 407 patients in the four-arm DKG 80-1 trial. The median follow-up was 8.2 years and a total of 537 relapses and 475 deaths were reported. At 8 years, the disease-free interval (DFI) rate was 32.4% and the overall survival (OS) rate was 40.0%. In terms of the DFI, the hazard ratio estimates (95% Confidence Intervals (CI)) were: 1.04 (0.84, 1.30) for the comparison of rIFN-α2b versus control, 0.96 (0.77, 1.20) for rIFN-γ versus control, and 1.32 (0.93, 1.87) for Iscador M® versus control. In terms of OS, the corresponding estimates (95% CI) for the 3 treatment comparisons were: for IFN-α2b 0.96 (0.76, 1.21), for rIFN-γ 0.87 (0.69, 1.10) and for Iscador M® 1.21 (0.84, 1.75), respectively. The results show no clinical benefit for adjuvant treatment with low dose rIFN-α2b or rIFN-γ or with Iscador M® in high-risk melanoma patients.
Available online 27 November 2003
Gesehen am 25.11.2020